Exploring the Impact of the STAD Cooperative Learning Model on Learning Outcomes in Vocational High Schools - Wila Mutiara Yeni; Ilmiyati Rahmy Jasril; Sartika Anori; Kenan Işık; Xue Wan (Journal of Hypermedia & Technology-Enhanced Learning, 2023)
This study examines the impact of the Student Team Achievement Division (STAD) cooperative learning model on student learning outcomes in technical education, specifically focusing on "The Application of Electronic Circuits" at SMKN 1 Sutera. The study employed a quasi-experimental design in which two classes were selected as samples: an experimental group taught using the STAD model and a control group utilizing direct instruction. Posttest results revealed that the experimental group achieved significantly higher average scores (80.00) compared to the control group (71.43), with a lower standard deviation (9.40) indicating more consistent learning outcomes. Normality and homogeneity tests confirmed the validity of the dataset, while hypothesis testing (tcalculated = 5.73, ttable = 1.679, α = 0.05) demonstrated the significant effectiveness of the STAD model. The findings highlight STAD’s ability to foster collaboration, inclusivity, and equitable learning, effectively bridging theoretical knowledge and practical skills gaps. This research addresses a gap in the application of cooperative learning models within technical education and offers actionable insights for enhancing teaching strategies in vocational contexts. Future studies should explore the long-term effects of STAD on skill application, student motivation, and knowledge retention, contributing to the broader discourse on innovative pedagogical approaches in education.